Development of the “TeachABK” Big Book to Improve the Speaking Skills of Children with Speech Delay - Reni Fadhilah; Sovi Amalia; Aunia Shifni El Wardah; Ratna Nulinnaja (Universitas Pendidikan Mandalika, 2026)
This study aims to develop a learning instrument, the